Food wars! = Shokugeki no soma. 21 - Tsukuda, Yuto, 1989- (Shonen Jump advanced., 2017)
In the frigid north of Hokkaido, Totsuki's first-year students face their greatest challenge yet the advancement exams! Dean Azami sees Soma and the gang as resisters of his administration, so he hits them with everything he's got, fair or not. Will the kids find a way to triumph over his shady tactics and advance to their second year, or will Azami freeze them in their tracks?!